Observational study on the safety profile of gadoterate meglumine in 35, 499 patients: The SECURE study. Issue 4 (11th October 2016) - Soyer, Philippe; Dohan, Anthony; Patkar, Deepak; Gottschalk, Andreas
Abstract : Purpose: To investigate the safety of gadoterate meglumine and identify the incidence of nephrogenic systemic fibrosis (NSF). Materials and Methods: An international prospective observational study was conducted from November 2008 to June 2013. A total of 35, 499 adults and children who were scheduled to undergo contrast‐enhanced MRI using gadoterate meglumine were analyzed (female, 53.1%; mean age: 49.5 years; range: 0‐98 years). At least 3‐month follow‐up was planned for patients with an estimated creatinine clearance or glomerular filtration rate <60 mL/min (/1.73 m2) to detect any suspicion or occurrence of NSF. Adverse events (AEs) were prospectively recorded. Demographic data, risk factors, indications for MRI examinations, characteristics of gadoterate meglumine administration, and efficacy were documented. Results: MRI examinations were mainly for central nervous system (61%). The most frequent risk factor was renal insufficiency (14.7%). Seventy AEs were observed in 44 patients (0.12%). Among the 70 AEs, 38 in 32 patients (0.09% of all patients) were considered related to gadoterate meglumine and classified as adverse drug reaction (ADR).The most frequent ADRs were urticaria (9 patients, 0.03%), nausea (7 patients, 0.02%), and vomiting (4 patients, 0.01%). Within the pediatric population (1, 629 patients), only one AE (vomiting) was observed. Nine adult patients (0.03%) experienced serious AEs. Moderate to severe renal insufficiency at inclusion was reported in 514 patients (1.5%). Among them, 476 (92.6%) were followed‐up. No patients were suspected of having NSF and no cases of NSF were observed. Conclusion: Our study confirms the excellent safety profile of gadoterate meglumine in routine practice. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:988–997